K‐MING: A mobile proxy handoff control scheme for proximate group‐based geodata sharing. (23rd October 2017) - Huang, Chung‐Ming; Mai, Chia‐Ming
Summary: This work adopts a mobile social network in proximity (MSNP)–centric group touring service concept to share geo–points of interest's (POIs') data among mobile users belonging to the same touring group. In a group‐based touring service, a mobile user can create a group in the MSNP that can consist of some clusters in which some members having the 3G/3.5G/4G cellular network service are selected as cluster leaders to enable their Wi‐Fi hot spot functions as mobile proxies. After that, each group member can join one of the clusters by connecting with a cluster leader's Wi‐Fi hot spot. Thereafter, each cluster leader downloads geo‐POIs' data using 3G/3.5G/4G cellular network and then shares the downloaded POIs' data with its cluster members through its Wi‐Fi hot spot. This work proposed a handoff mechanism such that each mobile user can handoff from its currently connected cluster to the other one that belongs to the same MNSP group. The main handoff concern is that each handheld device only allows a limited number of handheld devices to connect with its Wi‐Fi hot spot at the same time. This work proposed a K‐member‐limited MSNP‐based INter Group handoff scheme called K‐MING to tackle the handoff problem. The performance analysis shows that K‐MING for the group touring scenario has better performance for the sharing of geo‐POIs' data downloading in terms of average power consumption and average downloaded data volume from 3G/3.5G/4G cellular network than that of the individual touring scenario.